THE ROLE OF FORENSIC ODONTOLOGY IN PERSONAL IDENTIFICATION: INDONESIAN PERSPECTIVE - Soedarsono, N; Untoro, E; Quendangen, AR; Atmadja, DS (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 1 (2008): Indonesian Journal of Legal and Forensic Sciences, 2008)
The central dogma of dental identification is the comparison between postmortem dentalremains and ante-mortem dental records to confirm the personal identity. In mass disasters happened inIndonesia this method is almost impossible, since the ante-mortem dental record was usually not available. Inthis situation, however, postmortem dental examination is still useful to find the other general personalinformation, such as race, age, sex, blood group, eating habit, etc that will reduce the number of suspects(presumptive identification). DNA analysis performed from dental materials, such as enamel, dentin, cementand pulp, will confirm the identity of suspected / alleged person. We will report our techniques in handlingsuch cases when ante-mortem data is not available based on several mass disasters in Indonesia, such asbombing cases, ship and airline accidents. In mass catastrophes and natural calamities, the primaryidentification method is based on the findings of fingerprint, forensic dentistry and DNA analysis. In realcase, most of the personal identification is based on the finding dental (odontology) evidences, since the teethare resistant to the environmental influence, and degradation compared to other parts of the body. It wasproven thorough our investigations, that even when we were not supported by ante-mortem dental records, theinformation from post mortem dental examination is always useful for personal identification. To reduce thepossibility of in-identified victims, in the future Indonesia needs to standardize dental record, make anation-wide forensic odontology curriculum in Dental School, and provide the forensic odontology and DVItrainings for dentist .
Keywords: forensic dentistry (odontology) – personal identification – DNA